URGENSI REFORMASI BIROKRASI DI PERGURUAN TINGGI DALAM PERSPEKTIF ISLAM - Mahmudi, Abdul Halim; Yunus, Nur Rohim; Hikmatiar, Erwin (JURNAL ILMU SYARIAH, 2023)
The purpose of this article is to describe, from an Islamic perspective, the urgency of bureaucratic reform in higher education. Important aspects of bureaucratic reform pertinent to Islamic higher education are highlighted in this article. The research methodology employs qualitative methods and a literature-based strategy. This article is based on a comprehensive analysis of the relevant literature, with references to primary sources such as the Qur'an and Hadith, as well as academic references on bureaucratic reform and higher education. This article's findings indicate that bureaucratic reform in higher education is crucial for enhancing the quality of education and services. The Islamic perspective emphasizes the importance of fairness, equity, transparency, accountability, professionalism, competence, participation, consultation, ethics, and integrity in the implementation of these reforms. Implementing Islamic values in bureaucratic reform can bolster the Islamic higher education system and provide greater benefits to society and Muslims in general. This article provides a better comprehension of the urgency of bureaucratic reform in higher education from an Islamic perspective, as well as a solid foundation for more effective and sustainable reform initiatives.